2021
DOI: 10.12688/f1000research.25943.2
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between pancreatic T2* values and pancreatic iron loading with cardiac dysfunctions,  hepatic and cardiac iron siderosis among Egyptian children and young adults with β-thalassaemia major and sickle cell disease: a cross-sectional study

Abstract: Background: Cardiac, hepatic and pancreatic T2* measured by magnetic resonance imaging (MRI) has been proven to be an accurate and non-invasive method for measuring iron overload in iron overload conditions. There is accumulating evidence that pancreatic iron can predict cardiac iron in young children because the pancreas loads earlier than the heart. The aim of our study was to assess the relationships between pancreatic T2* values and pancreatic iron loading with cardiac dysfunctions and liver and cardiac ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
4
4
0
Order By: Relevance
“…In accordance with previous studies in patients with SCD, 16,48 we observed that pancreatic R2* was directly correlated with ferritin and LIC. No correlation was found between pancreatic and cardiac R2*, likely because all patients had no cardiac iron.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous studies in patients with SCD, 16,48 we observed that pancreatic R2* was directly correlated with ferritin and LIC. No correlation was found between pancreatic and cardiac R2*, likely because all patients had no cardiac iron.…”
Section: Discussionsupporting
confidence: 93%
“…The significant association of pancreatic R2* values with serum ferritin levels and MRI LIC values is in agreement with a previous study on a smaller population, including children with both TM and sickle cell disease 40 . Importantly, in our study, the MRI LIC provided a superior discriminatory ability for pancreatic IO compared to serum ferritin levels.…”
Section: Discussionsupporting
confidence: 92%
“…Due to the low number of patients with myocardial IO, we could not perform a ROC curve analysis to detect the best pancreatic R2* cutoff for the prediction of significant myocardial siderosis. The discrepancy with two previous studies on pediatric patients that failed to detect a correlation between pancreatic and cardiac iron can be explained by the smaller sample size of these studies and the different backgrounds of the patients 24,40 . It deserves mention that the comparison with the study by Salama et al.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations